2017
DOI: 10.3389/fimmu.2017.00777
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the Epstein–Barr Viral Antigen Latent Membrane Protein 1 Induces Myelin-Reactive Antibodies In Vivo

Abstract: Multiple sclerosis (MS) is an autoimmune chronic inflammatory disease of the central nervous system (CNS). Cross-reactivity of neuronal proteins with exogenous antigens is considered one of the possible mechanisms of MS triggering. Previously, we showed that monoclonal myelin basic protein (MBP)-specific antibodies from MS patients cross-react with Epstein–Barr virus (EBV) latent membrane protein 1 (LMP1). In this study, we report that exposure of mice to LMP1 results in induction of myelin-reactive autoantibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…Substantial support in favour of its involvement in multiple sclerosis (MS), an autoimmune chronic inflammatory disease of the central nervous system, with the backdrop of molecular mimicry came in 2017, when Lomakin et al demonstrated homology between viral latent membrane protein 1 (LMP1) and myelin basic protein (MBP) of humans. Similarly, its association with autoimmune diseases such as SLE and RA has also been studied.…”
Section: Molecular Mimicry: the Conceptmentioning
confidence: 99%
“…Substantial support in favour of its involvement in multiple sclerosis (MS), an autoimmune chronic inflammatory disease of the central nervous system, with the backdrop of molecular mimicry came in 2017, when Lomakin et al demonstrated homology between viral latent membrane protein 1 (LMP1) and myelin basic protein (MBP) of humans. Similarly, its association with autoimmune diseases such as SLE and RA has also been studied.…”
Section: Molecular Mimicry: the Conceptmentioning
confidence: 99%
“…In 2003, cross-reactive recognition of the nuclear antigen of the Epstein-Barr virus (EBNA) and the autoantigen peptide of the myelin basic protein (MBP) by the monoclonal T cell receptor was demonstrated [61]. Later on, cross-reactivity was also detected and validated in autoantibodies to the LMP1 protein of the Epstein-Barr virus and MBP [62, 63]. In the case of EAE, Bregs can inhibit autoimmune T cell responses by slowing the differentiation of the pro-inflammatory T helpers 1 specific to CNS autoantigens [57].…”
Section: B Cell Regulation In the Development Of Autoimmune Pathologiesmentioning
confidence: 99%
“…Epstein-Bar virus (EBV) is also a well-known MS-associated virus and MBP-specific T cells cross-react to EBV peptides [ 41 , 42 ]. Another study showed that MBP-specific antibodies purified from MS patients cross-react to EBV latent membrane protein 1 [ 43 ]. Therefore, EBV-derived MBP mimotopes may be involved in disease initiation and/or progression of MS.…”
Section: Discussionmentioning
confidence: 99%